ANALISIS PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI LQ 45 PERIODE 2015 – 2017 - Teresia Agnes; Martha Ayerza Esra (Jurnal Manajemen, 2019)
Maximizing the value of a company is important for the company, because the higher the value of acompany, the better and more feasible for investors to invest. Therefore the company must be careful inmaking policy decisions considering that every financial decision can affect the value of the companyand have an impact on achieving the objectives of the company. The underlying theory of the formationof this research is signaling theory, bird in the hand theory, and the theory of the firm. Signaling theoryexplains how information reported impacts society. Bird in the hand theory explains the impact ofdividend distribution in a company. Theory of the firm explains the characteristics of the company in aneffort to maximize profits. This research was conducted on companies contained in the LQ 45 Index listedon the Indonesia Stock Exchange in the period 2015 - 2017. Using a purposive sampling method obtaineda sample of 24 companies with the help of SPSS 22 program. The data analysis technique used is multiplelinear regression. The results of this study indicate that the regression model used has met the classicalassumption test. The results of the tests conducted indicate that data can be backed up. The test resultsare normally distributed and pass the classical assumption test (Normality, Multicolonity,Heteroscedasticity, and Autocorrelation). The results of the study show that (1) Profitability has an effecton Company Values, (2) Capital Structure has an effect on Company Values, and (3) Dividend Policieshave an effect on Company Values.